Perceptions and Expectations of Students From Pre-prosperous Families on Islamic Education at Pesantren - Firmansyah Firmansyah (Islamic University of Indonesia, 2022)
This study elaborates on the perceptions and expectations of students from pre-prosperous families towards Islamic education held at the Pondok Pesantren Darul Muttaqien Kayuagung during the Covid-19 pandemic. This study employs a phenomenological approach. This study concludes that policies offering convenience and flexibility in paying tuition are mostly accountable for the santri selecting them over public educational institutions. The majority of respondents believe that the benefits of graduating from an Islamic boarding school include an improvement in their status in the community due to their position as ustadz or ustadzah or having a respectable career to raise their standard of living. This study confirms the belief that Islamic boarding schools serve the community as moral education centers and as social institutions that accommodate the educational needs of students from pre-prosperous families. The findings of this study support Paulo Freire's conscientization theory, which holds that education can inspire individuals to take action to improve socio-cultural realities by mobilizing themselves to progress their social status.